Upaya Meningkatkan Kemampuan Berpikir Kritis Melalui Pembelajaran Sains Pada Anak Usia 4-5 Tahun - Robiatul Adawiah; Enok Hani (LPPM STAI La Tansa Mashiro, 2024)
This study was motivated by the discovery of several children in the Semai Benih Bangsa At-Taghyir Playgroup who showed that their critical thinking skills were not optimal. This can be seen from the child's curiosity is still low, the child is not active in the learning process and the few children who ask questions while learning. This study aims to determine the critical thinking skills of children aged 4-5 years and to determine the increase in critical thinking skills in children aged 4-5 years after being given science learning. This type of research is Classroom Action Research with the Kemmis and Tagart model which uses a spiral system where each cycle consists of four stages, namely planning, action, observation and reflection. Data acquisition in this study used interview, observation and documentation techniques. The application of science learning by conducting science experiments of running water, rainwater, tap water, candle fire, floating and sinking eggs and egg foam science experiments can improve critical thinking skills in children aged 4-5 years at the Semai Benih Bangsa At-Taghyir Playgroup, Jawian Serang-Banten. This is evident from the pre-cycle of 39.6% which increased to 63.1% in cycle I and reached 87.9% in cycle II.The conclusion of this study is that science learning can improve critical thinking skills in children aged 4-5 years in the At-Taghyir Nation Seeds Playgroup, Jawilan Serang-Banten.